PENDAFTARAN PELAKSANAAN PUTUSAN ARBITRASE ASING YANG BELUM FINAL - Wijaya, Cindy (JURNAL MERCATORIA, 2019)
Indonesia regulates International Arbitration in the Article 65 to Article 69 of Law Number 30 of 1999. The registered award must always fulfil the requirements in Article 66 in order to be admitted and proceeded, and the applied awards must fulfil the requirements in article 67 in order to obtain exequatur. When the requirements do not meet the terms of engagement, as if the award is not finalized or in an appeal process or put aside, Indonesia may declare to refuse the enforcement. The purpose of the study was to find out about the application of foreign arbitration awards and the response of the District Court of Central Jakarta towards the applied award if the application of the foreign arbitration had not been finalized yet. The result and the discussion was that Law Number 30 of 1999 has not regulate in detail on how the foreign arbitration award can be refused, Therefore, it is necessary to have an amendment and a more detailed regulation on the requirements of application and the reasons for refusing foreign arbitration awards.